HUBUNGAN TINGKAT STRES DENGAN GANGGUAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMKN 03 PEKANBARU - Emi Yulita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Every woman experiences menstrual cycle irregularity, menstrual cycle usually can go forward and backward within a few days, especially in adolescents, it is caused by sexual hormones unstable. Irregularity of the menstrual cycle is due to several factors, including physical factors (such as fatigue) and psychological factors (stress). The purpose of research to determine the correlation between stress and menstrual cycle disorders in adolescent girls in the class III SMKN 03 Pekanbaru. This study used cross sectional type of study is research analytically. The research was conducted at SMK 03 Pekanbaru on August. With a population of 161 people and sebayak sample of 115 with a random sample sampling. Means of collecting data using questionnaires. Analysis of the data used are univariate and bivariate. The results showed that there is a correlation between stress and menstrual cycle disturbances obtained value of P = 0.000 with significance level is 0.05 (0.000